Giant transit thrombus—From right to left. Issue 7 (19th June 2020) - Djordjevic, Ilija; Drinhaus, Hendrik; Ivanov, Borko; Eghbalzadeh, Kaveh; Gerfer, Stephen; Sabashnikov, Anton; Kuhn‐Regnier, Ferdinand; Mader, Navid; Wahlers, Thorsten; Rahmanian, Parwis
Abstract: Pulmonary embolism can be associated with paradox embolism requiring immediate surgical therapy regardless of hemodynamic status. Here we present images illustrating a giant transit thrombus as a concomitant finding in a patient with pulmonary artery embolism.